A portable automatic endpoint detection system for amplicons of loop mediated isothermal amplification on microfluidic compact disk platform - Ibrahim, Fatimah; Uddin, S.M.; Sayad, A.A.; Pei, K.X.; Thiha, A.; Mohktar, M.S.; Hashim, U.; Cho, J.; Thong, Kwai Lin (Multidisciplinary Digital Publishing Institute, 2015)
In recent years, many improvements have been made in foodborne pathogen detection methods to reduce the impact of food contamination. Several rapid methods have been developed with biosensor devices to improve the way of performing pathogen detection. This paper presents an automated endpoint detection system for amplicons generated by loop mediated isothermal amplification (LAMP) on a microfluidic compact disk platform. The developed detection system utilizes a monochromatic ultraviolet (UV) emitter for excitation of fluorescent labeled LAMP amplicons and a color sensor to detect the emitted florescence from target. Then it processes the sensor output and displays the detection results on liquid crystal display (LCD). The sensitivity test has been performed with detection limit up to 2.5 × 10−3 ng/µL with different DNA concentrations of Salmonella bacteria. This system allows a rapid and automatic endpoint detection which could lead to the development of a point-of-care diagnosis device for foodborne pathogens detection in a resource-limited environment.